2015
DOI: 10.1128/cvi.00763-14
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Three Fully Human Toxin A- and Toxin B-Specific Monoclonal Antibodies Protects against Challenge with Highly Virulent Epidemic Strains of Clostridium difficile in the Hamster Model

Abstract: C lostridium difficile infection (CDI) is a leading cause of pseudomembranous colitis and diarrhea (C. difficile-associated diarrhea [CDAD]) causally related to a perturbation of the intestinal microbiota due to antibiotic use. Although the transmission of CDI is primarily associated with health care and long-term care facilities, C. difficile is a ubiquitous microorganism that has been found in the environment. There are documented cases of community-acquired CDI; in fact, the community-acquired C. difficile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 44 publications
(60 reference statements)
0
35
0
Order By: Relevance
“…This hypothesis is supported by data from a study in which a cocktail of monoclonal antibodies directed against TcdA and TcdB was administered intraperitoneally to hamsters prior to C. difficile challenge. This approach was found to protect against GI damage and death from CDI (149,150). The administration of the TcdB-reactive antibody bezlotoxumab in combination with either metronidazole or vancomycin has also been shown to decrease rates of CDI recurrence in humans (151).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…This hypothesis is supported by data from a study in which a cocktail of monoclonal antibodies directed against TcdA and TcdB was administered intraperitoneally to hamsters prior to C. difficile challenge. This approach was found to protect against GI damage and death from CDI (149,150). The administration of the TcdB-reactive antibody bezlotoxumab in combination with either metronidazole or vancomycin has also been shown to decrease rates of CDI recurrence in humans (151).…”
Section: Other Mechanisms Of Action Of Beneficial Microbes and Probiomentioning
confidence: 99%
“…Immunization with recombinant RBDs represents a promising method in vaccine development [22,23]. A number of studies have demonstrated that antibodies induced by RBD-based vaccines can efficiently block the toxicity of bacterial or viral replication in tissue [27]. Several C. difficile vaccine candidates exist worldwide [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Obiltoxaximab, a mAb targeting protective antigen (PA), a component of anthrax lethal toxin (LT) and edema toxin (ET) required for toxin entry, prevents dissemination of Bacillus anthracis and reduces mortality in pre- and post-exposure rabbit or cynomolgus macaque models of inhalational anthrax, a foremost biodefense concern [19]. A cocktail of one fully human MAb specific to the receptor binding domain of Clostridium difficile toxin A and two fully human MAbs specific to nonoverlapping regions of the glucosyltransferase domain of C. difficile toxin B reduced severity and duration of diarrhea and mortality upon challenge with highly virulent C. difficile strains [20]. Lastly, an interesting derivation of mAb therapeutics was reported in the treatment of difficult S. aureus infections, where a slow-growing intracellular reservoir of the pathogen is often resistant to antibiotic clearance.…”
Section: Neutralization Of Virulence Factors: Disarming the Pathogenmentioning
confidence: 99%